FEMALE TRADITIONAL GENDER ROLES IN THE BROTHERS GRIMMS' SLEEPING BEAUTY: AN ACTANTIAL MODEL ANALYSIS - Jeanyfer Tanusy; Trisnowati Tanto (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2023)
The tale of the Sleeping Beauty is still one of the well-loved and popular fairy tales among children, especially girls. The story has been adapted into various versions but has not changed essentially—it is always about a princess saved from a curse, about good versus bad. Due to the simple nature of the story, most literary researchers no longer deem this story a valuable source of data anymore although there are still more to uncover from the fairy tale. This study attempts to examine how the female characters in the story are represented from the structural semiotics perspective using two theories proposed by A. J. Greimas, namely the Actantial Model and the Narrative Trajectory. The qualitative method is applied to interpretatively divide the story into different major events, from which an actantial diagram and a trajectory can be made before the representation is drawn. The findings suggest that the female characters in the story are mostly placed as an object of the actantial diagram and a goal in the trajectory; this means that the story puts the female characters in passive roles that comply to the traditional gender roles and female stereotypes.